ANALYTICAL REVIEW OF THE METHODS FOR DETERMINING WATER ACTIVITY IN NON-SMOKING TOBACCO AND NON-SMOKING NICOTINE-CONTAINING ORAL PRODUCTS - N. A. Pankov (Новые технологии, 2022)
The article presents an analytical review of the methods for determining the activity of water in food products. This is necessary in order to select among several methods the most suitable, which can be taken as a basis for further development of the methodology for determining water activity for non-smoking tobacco and nicotine-containing products.Water activity is an indirect indicator of microbiological contamination and is particularly important for tobacco and non-tobacco products consumed directly without burning. When water activity values are relatively high in Non-tobacco nicotine-containing products of oral type (NTNCPOT), microflora can develop. Non-tobacco nicotine-containing oral consumption products are actively marketed and are partially replacing traditional nicotine “consumption” methods. A distinctive feature of this product is its method of consumption, which is that as a result of consumption there is no process of inhaling tobacco smoke, which has a negative impact on the human body. On this basis, this product is a less dangerous alternative to smoking cigarettes. Since the products are so widespread, it is necessary to establish quality control. Water activity is not a standard indicator for controlling tobacco products, but since these products are intended for oral consumption, this indicator should begin to be defined as one of the most important for consumer safety. For non-smoking tobacco and nicotine-containing oral products, the CORESTA CRM88 method is the most appropriate. In order to develop a methodology for determining water activity and establishing the necessary values, further study of smokeless tobacco products and non-smokeless nicotine-containing oral products is needed.